2022
DOI: 10.3389/fviro.2022.956113
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate and Isoquercetin Synergize With Remdesivir to Reduce SARS-CoV-2 Replication In Vitro

Abstract: The ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) urgently needs effective antivirals. After over 2 years since the beginning of the pandemic, only a few FDA approved therapeutic options are available to treat the population. Combination therapies have become a standard for the treatment of other infectious diseases such as HIV and hepatitis C due to their improved efficacy compared to monotherapy, reduced toxicity, the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In a separate study, all types of catechins, including ECGC, indicated a considerable affinity to the S protein of the SARS-CoV-2 virus 163 . Moreover, Rabezanahary et al demonstrated the inhibitory effects of EGCG and isoquercetin against SARS-CoV-2 in vitro and proved their substantial antiviral synergistic effects with remdesivir 164 .…”
Section: Flavonoidsmentioning
confidence: 99%
“…In a separate study, all types of catechins, including ECGC, indicated a considerable affinity to the S protein of the SARS-CoV-2 virus 163 . Moreover, Rabezanahary et al demonstrated the inhibitory effects of EGCG and isoquercetin against SARS-CoV-2 in vitro and proved their substantial antiviral synergistic effects with remdesivir 164 .…”
Section: Flavonoidsmentioning
confidence: 99%
“…Similarly, emodin found in rhubarb roots ( Rheum officinale ) showed inhibitory effects by obstructing the SGp–ACE2 interaction in a cell‐free competition assay with an IC 50 of 200 μM 20 . An in vitro study revealed that epigallocatechin‐3‐ O ‐gallate (EGCG) and isoquercetin are potent against SARS‐CoV‐2 and demonstrated synergistic antiviral effects with remdesivir 21 . The use of polyphenols is also a valuable therapeutic strategy to treat COVID‐19 due to their antiviral, antioxidant, antithrombotic, anticancer, antidiabetic, anti‐inflammatory, and prebiotic effects 21–26 .…”
Section: Introductionmentioning
confidence: 99%
“…20 An in vitro study revealed that epigallocatechin-3-O-gallate (EGCG) and isoquercetin are potent against SARS-CoV-2 and demonstrated synergistic antiviral effects with remdesivir. 21 The use of polyphenols is also a valuable therapeutic strategy to treat COVID-19 due to their antiviral, antioxidant, antithrombotic, anticancer, antidiabetic, antiinflammatory, and prebiotic effects. [21][22][23][24][25][26] Naturally occurring polyphenols are easily accessible and inexpensive to produce and have low toxicity, making them potential drug candidates for treating virus-induced inflammatory diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro activity has also been shown for severe-acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [14,[17][18][19][20], hepatitis C virus (HCV) [21,22], herpes simplex virus (HSV-1), vaccinia virus (VACV), adenovirus (AdV), reovirus (RV) [16], and others. Colpitts and Schang [16] have shown that EGCG interacts with several viruses (HCV, HSV-1, VACV, AdV, RV, and IAV) surface proteins and postulate that inhibition of influenza virus may be due to EGCG binding to the influenza surface glycoprotein haemagglutinin (HA) [16,18,23].…”
Section: Introductionmentioning
confidence: 99%